2018
DOI: 10.1158/0008-5472.can-17-3703
|View full text |Cite
|
Sign up to set email alerts
|

miRNA Profiling of Magnetic Nanopore–Isolated Extracellular Vesicles for the Diagnosis of Pancreatic Cancer

Abstract: Improved diagnostics for pancreatic ductal adenocarcinoma (PDAC) to detect the disease at earlier, curative stages and to guide treatments is crucial to progress against this disease. The development of a liquid biopsy for PDAC has proven challenging due to the sparsity and variable phenotypic expression of circulating biomarkers. Here we report methods we developed for isolating specific subsets of extracellular vesicles (EV) from plasma using a novel magnetic nanopore capture technique. In addition, we prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 56 publications
(65 reference statements)
0
54
0
Order By: Relevance
“…There is growing evidence suggested the potential role for sEVs in early detection of many diseases [27–30]. However, systematic screening of plasma sEVs derived early CC biomarkers has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence suggested the potential role for sEVs in early detection of many diseases [27–30]. However, systematic screening of plasma sEVs derived early CC biomarkers has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although considerable previous research on determining the usefulness of miRNA as biomarkers has focused on analysis of tissue specimens, other researchers have focused on circulating miRNA as a potential diagnostic and prognostic biomarker. [8][9][10] Recently, miR-1246 and miR-1290 were identified as tumor-initiating, cell-specific miRNAs in non-small cell lung cancer. 11,12 Moreover, serum miR-1246 and miR-1290 levels were correlated with the clinical response of patients with lung cancer who were receiving chemotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that miR-30e could be transferred by cholangiocarcinoma (CCA) cell-derived EVs, and suppress recipient CCA cell invasion and migration (18). In PDAC, some investigators reported that EVencapsulated miRNAs, such as miR-196a, miR-1246, or miR-4644, could contribute to tumor development and play crucial roles in the diagnosis as tools of liquid biopsy (19)(20)(21). Therefore, we focused on identifying the mechanisms of ncRNA transfer by PDAC-derived EVs and investigated their contributions to PDAC development.…”
Section: Introductionmentioning
confidence: 99%